Phototactic behavior 7: phototactic response of the maize weevil, Sitotroga zeamais motsch (Coleopter: Curculionidae), to light-emitting diodes - Park, J.H., Chonbuk National University, Jeonju, Republic of Korea; Sung, B.K., Chonbuk National University, Jeonju, Republic of Korea; Lee, H.S., Chonbuk National University, Jeonju, Republic of Korea (Applied biological chemistry, 2015)
Phototactic responses of maize weevil, Sitotroga zeamais, adults to five light-emitting diodes (LEDs) were evaluated and compared with the commonly used luring lamp (BLB). Under optimal light conditions, the red LED (625 +- 10 nm) exhibited the highest attraction rate (59.8 %), followed by the yellow LED (590 +- 5 nm, 52.3 %), the infrared LED (730 nm, 51.9 %), the green LED (520 +- 5 nm, 46.7 %), the blue LED (470 +- 10 nm, 45.3 %), the ultraviolet LED (365 nm, 32.7 %), and the BLB (27.3 %). Moreover, the red LED was approximately 2.19 times more attractive than that of the BLB. These results indicate that a red LED trap may be useful to control S. zeamais adults.